(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents decolonial methodologies for creation in dance and performance, centered on the urgent needs of racialized bodies from a higher education perspective. In response to the marginalization of Black epistemologies in curricula, it proposes three practical-theoretical axes— Corpo Peça, Utopias de Si, and Corpo Báskula—developed from the author’s experience as a Black artist-teacher and in dialogue with thinkers such as Nêgo Bispo, Inaicyra Falcão, Leda Maria Martins, Audre Lorde, and Patricia Hill Collins.